STUDENTS’ NUMERACY SKILLS IN SOLVING THE FOURTH LEVEL OF MINIMUM COMPETENCY ASSESSMENT QUESTION DEVELOPMENT ON RATIO AND PROPORTION - Diah Lutfiana Dewi; Rooselyna Ekawati (MATHEdunesa, 2022)
Abstract Minimum Competency Assesment measures two basic competencies, namely reading literacy and numeracy literacy. PISA results showed that the Indonesian students’ ability in the mathematics category is relatively low. Numeracy is an ability to use mathematics to solve daily life problems. One of the closely related to everyday life mathematical topics is ratio and proportion. However, there are still many students’ difficulties in solving problems related to ratios and proportions which are basically the basis concept for mathematical knowledge and science understanding. Therefore, it’s necessary to conduct a students' numeracy skills analysis related to ratios and proportions in order to facilitate the process in improving students' abilities. This study aims to describe students' numeracy skills in solving the AKM questions development on ratio and proportion with a qualitative descriptive approach. The subjects of this study were 8th grade students who participate in AKM. Researcher used test and interviews as collect data techniques which was then analyzed in three stages, namely data reduction, data presentation, and verification. The result showed that there are students' numeracy skills indicators that haven’t been fully achieved, including students' ability to analyze information presented in various forms (diagrams, tables, etc.) and to interpret the analysis results to make decisions. While the most often appear indicator is the students’ ability to use various kinds of numbers or symbols to solve daily life problems. The results of this study can be used as a basis for adjusting learning models and strategies as an effort to improve students' numeracy skills. Keywords: numeracy skills, AKM, ratio and proportion. Abstrak Asesmen Kompetensi Minimum mengukur dua kompetensi mendasar, yakni literasi membaca dan literasi numerasi. Hasil PISA menunjukkan bahwa kemampuan siswa Indonesia dalam kategori matematika relatif rendah. Numerasi merupakan kemampuan seseorang dalam menggunakan matematika untuk menyelesaikan permasalahan dalam kehidupan sehari-hari. Salah satu topik matematika yang berkaitan erat dengan kehidupan sehari-hari adalah rasio dan proporsi. Akan tetapi, masih banyak ditemukan kesulitan yang dialami oleh siswa dalam menyelesaikan permasalahan terkait rasio dan proporsi yang pada dasarnya merupakan konsep dasar untuk pemahaman konsep pengetahuan matematika maupun sains. Oleh karena itu, perlu dilakukan suatu analisis terhadap kemampuan numerasi siswa terkait rasio dan proporsi guna memfasilitasi proses dalam meningkatkan kemampuan siswa. Penelitian ini bertujuan untuk mendeskripsikan kemampuan numerasi siswa dalam menyelesaikan pengembangan soal AKM pada subdomain rasio dan proporsi dengan pendekatan deskriptif kualitatif. Subjek penelitian ini adalah siswa kelas 8 yang terpilih sebagai peserta AKM. Peneliti menggunakan tes dan wawancara sebagai teknik untuk mengumpulkan data yang kemudian dianalisis dengan tiga tahapan, yakni reduksi data, penyajian data, dan verifikasi data. Hasil penelitian menunjukkan bahwa terdapat indikator kemampuan numerasi siswa yang belum sepenuhnya tercapai, yakni kemampuan siswa dalam menganalisis informasi yang disajikan dalam berbagai bentuk (grafik, diagram, tabel, dan sebagainya) dan kemampuan siswa dalam menafsirkan hasil analisisnya untuk mengambil keputusan. Sedangkan indikator yang paling sering muncul adalah kemampuan siswa dalam menggunakan berbagai macam angka atau simbol untuk menyelesaikan kehidupan sehari-hari. Hasil penelitian ini dapat digunakan sebagai dasar untuk penyesuaian model dan strategi pembelajaran sebagai upaya untuk meningkatkan kemampuan numerasi siswa. Kata Kunci: kemampuan numerasi, AKM, rasio dan proporsi.